Designs and materials of flexible wearable microstrip patch antennas: a systematic review - Ayano Koyrita Banale; Kinde Anlay Fante; S. Sathiesh Kumar; Aruna Sampath (Discover Applied Sciences)
Abstract Research into enhancing the performance and flexibility of wearable microstrip patch antennas has emerged as a cutting-edge field, attracting significant attention from researchers globally. However, an adequate solution that leads to high antenna performance with high flexibility has not yet been found. Various research papers are analyzed from seven well-known online repositories and databases: IEEE Xplore, Directory of Open Access Journals, Science Direct, Springers Link, MDPI, Wiley Online Library and Google Scholar. In this study, three research questions concerning the types of materials and designs used and their impact on the performance of flexible wearable microstrip patch antennas are addressed. To investigate solutions to these questions, 46 related papers were identified via scientifically accepted review planning and conducting processes. Special focus is given to 2.5 GHz inset/strip line feeds with rectangular microstrip patch antennas. We found that copper-based conductive strips are widely used for flexible wearable microstrip patch antennas with high performance and low flexibility. On the other hand, newly emerging polymers, including graphene, PEDOT:PSS, PPy, and polyaniline, are also used in flexible microstrip patch antennas with low performance and high flexibility. Challenges and future research directions of the flexible wearable microstrip patch antennas’ current status are presented.